The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00534-009-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) after pancreaticoduodenectomy: proposal of a postoperative NAFLD scoring system

Abstract: In conclusion, NAFLD develops frequently in patients who undergo PD, and some patients even progress to NASH. A postoperative NAFLD scoring system makes it possible to predict the occurrence of NAFLD after PD, and aggressive nutrition support is needed for patients with high scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
179
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(192 citation statements)
references
References 27 publications
9
179
4
Order By: Relevance
“…Similar to our results, in the previous randomized control trial between PPPD and conventional PD, the nutritional status including the postoperative weight loss was comparable between PPPD and conventional PD groups [13,14]. On the other hand, Kato et al [35] reported eating disorders other than pancreatic dysfunction after pancreatectomy were an important risk factor for NAFLD after pancreatectomy, and postoperative malnutrition associated with DGE and digestive disturbance due to complicated reconstruction leads to the development of NAFLD. Previous studies have revealed that the decrease in the hepatic CT value reflects the degree of fat deposition within the liver [23,36].…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our results, in the previous randomized control trial between PPPD and conventional PD, the nutritional status including the postoperative weight loss was comparable between PPPD and conventional PD groups [13,14]. On the other hand, Kato et al [35] reported eating disorders other than pancreatic dysfunction after pancreatectomy were an important risk factor for NAFLD after pancreatectomy, and postoperative malnutrition associated with DGE and digestive disturbance due to complicated reconstruction leads to the development of NAFLD. Previous studies have revealed that the decrease in the hepatic CT value reflects the degree of fat deposition within the liver [23,36].…”
Section: Discussionsupporting
confidence: 80%
“…These findings suggest that the mechanisms underlying NAFLD after PD differ from those causing NAFLD associated with metabolic syndrome. Recent studies have also suggested that pancreatic exocrine insufficiency may cause NAFLD after PD [8,9] . Although only univariate analyses were examined in our study, pancreatic cancer was associated with the development of NAFLD, which is considered to lead to impaired pancreatic exocrine functions due to obstruction of the MPD, in turn resulting in obstructive distal pancreatic atrophy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown strong relationships among NAFLD associated with metabolic syndrome, hepatic insulin resistance and type 2 diabetes mellitus [5][6][7] . On the other hand, NAFLD sometimes develops after pancreatoduodenectomy (PD) [8] . Tanaka et al [9] recently reported that NAFLD after PD was characterized by non-obesity and a lack of both hyperlipidemia and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A Japanese group proposed a scoring system to predict the development of NAFLD using data of 54 cases, which included 5 components of pancreatic carcinoma, extent of pancreatic resection, pancreatic texture, postoperative diarrhea, and postoperative eating disorder. The authors suggested that their scoring system makes it possible to predict the occurrence of NAFLD after pancreaticoduodenectomy, and aggressive nutrition support is needed for patients with high scores [27]. Postoperative malnutrition associated with delayed gastric emptying and digestive disturbance due to complicated reconstruction, postoperative insulin resistance and other various risk factors leads to the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%